Ad hoc posterior tibial vessels perforator propeller flaps for the reconstruction of lower third leg soft- tissue defects - Balakrishnan, Thalaivirithan Margabandu; Ramkumar, Jayagosh; Jaganmohan, Janardhanan (Indian Journal of Plastic Surgery, 2017)
Introduction: Lower third leg soft tissue defects with anatomical and pathological constraints are posing formidable challenges to reconstructive surgeon. Aim: This retrospective study was conducted to assess the effectiveness of ad hoc posterior tibial vessels perforator-propeller flaps for the reconstruction of small and medium sized soft tissue defects in the lower third leg. Patients and Methods: 22 patients (16 were males and 6 were females) were involved in this study between period of January 2012 and December 2016. We followed the protocol of initial non delineating exploratory incision made to find out single best perforator in all patients. All the defects in leg reconstructed with adhoc posterior tibial vessel propeller flaps. Results: All 22 flaps survived well. All in an average of 13 months follow up period, had pain free walking, with minimal scarring and acceptable aesthesis at the reconstruction sites with no need for any secondary procedure. Conclusion: With inability of preoperatively dopplering the perforators in the lower third leg region, the exploratory posterior nondelineating incision was used in all cases to secure the single best perforator for the propeller flaps. Thus adhoc posterior tibial vessel propeller flaps are dependable, easily adoptable for the reconstruction of soft tissue defects of the lower third leg region.
Keywords: Ad hoc posterior tibial vessel propeller flaps; exploratory non-delineating incision; extensile steps of skeletoniszation of perforator